Changing Nomads in a Changing World - Ginat, Joseph (Liverpool University Press, 1998)
Anthropologists discuss how pastoralists are coping and changing as the societies they inhabit change at an unprecedented rate. Joseph Ginat is the author of ""Blood Revenge: Family Honor, Mediation and Outcasting"", and Anatoly M. Khazanov is the author of ""Nomads and the Outside World"".